2018
DOI: 10.1103/physrevlett.121.123604
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Systems for the Generation of Nonclassical Mechanical States via Quadratic Interactions

Abstract: We present a method to implement two-phonon interactions between mechanical resonators and spin qubits in hybrid setups, and show that these systems can be applied for the generation of nonclassical mechanical states even in the presence of dissipation. In particular, we demonstrate that the implementation of a two-phonon Jaynes-Cummings Hamiltonian under coherent driving of the qubit yields a dissipative phase transition with similarities to the one predicted in the model of the degenerate parametric oscillat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 110 publications
(166 reference statements)
1
39
0
Order By: Relevance
“…In recent years, the driven-dissipative Bose-Hubbard model in presence of a two-photon -i.e. quadratic in the field -driving term has been studied both theoretically [19,25,[40][41][42][43][44][45][46][47][48][49] and experimentally [50,51]. This quadratically driven scheme has been in particular proposed as a possible realization of a noise-resilient quantum code, where photonic Schrödinger's cat states with even and odd photon number parity behave as interacting spin degrees of freedom [42][43][44][45]50].…”
mentioning
confidence: 99%
“…In recent years, the driven-dissipative Bose-Hubbard model in presence of a two-photon -i.e. quadratic in the field -driving term has been studied both theoretically [19,25,[40][41][42][43][44][45][46][47][48][49] and experimentally [50,51]. This quadratically driven scheme has been in particular proposed as a possible realization of a noise-resilient quantum code, where photonic Schrödinger's cat states with even and odd photon number parity behave as interacting spin degrees of freedom [42][43][44][45]50].…”
mentioning
confidence: 99%
“…In general, the coupling strength of the second sideband can reach 2π × 10 kHz, and the third sideband can reach 2π × 1 kHz. They are 3 orders of magnitude higher than what can be achieved with the direct second-or third-order coupling between a single spin and the mechanical mode [46].…”
Section: A the Mollow Sidebandmentioning
confidence: 73%
“…The multi-phonon interaction featuring nonlinearity is widely studied for the preparation of nonclassical motion states [46,58,59,63], which may have potential applications in quantum information, quantum metrology and quantum biology [64]. In this section, we discuss some applications based on the multi-phonon interaction.…”
Section: Applicationsmentioning
confidence: 99%
“…In order to induce the coupling between the mechanical mode and the NV centers, the magnetic gradient is usually required. [ 51–54 ] It has been found that both the first order magnetic gradient [ 36,55 ] and the second order magnetic gradient [ 56–58 ] can induce the strong coupling between the translational motion and the NV centers. Recent studies also show the possibility of strong coupling between the levitated torsional mode and the NV center in the uniform magnetic field.…”
Section: Manipulating Motional Modesmentioning
confidence: 99%